The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-29077-3
|View full text |Cite
|
Sign up to set email alerts
|

Ranking genome-wide correlation measurements improves microarray and RNA-seq based global and targeted co-expression networks

Abstract: Co-expression networks are essential tools to infer biological associations between gene products and predict gene annotation. Global networks can be analyzed at the transcriptome-wide scale or after querying them with a set of guide genes to capture the transcriptional landscape of a given pathway in a process named Pathway Level Coexpression (PLC). A critical step in network construction remains the definition of gene co-expression. In the present work, we compared how Pearson Correlation Coefficient (PCC), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 48 publications
2
48
0
Order By: Relevance
“…A recent study focused on microarray and RNA‐seq based global and targeted co‐expression networks in Arabidopsis (Liesecke et al., ). This study identified Pathway Level Co‐expression using a set of guide genes, and compared how Pearson Correlation Coefficient (PCC), Spearman Correlation Coefficient (SCC), their respective ranked values (Highest Reciprocal Rank (HRR)), Mutual Information (MI) and Partial Correlations (PC) performed on global networks.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study focused on microarray and RNA‐seq based global and targeted co‐expression networks in Arabidopsis (Liesecke et al., ). This study identified Pathway Level Co‐expression using a set of guide genes, and compared how Pearson Correlation Coefficient (PCC), Spearman Correlation Coefficient (SCC), their respective ranked values (Highest Reciprocal Rank (HRR)), Mutual Information (MI) and Partial Correlations (PC) performed on global networks.…”
Section: Discussionmentioning
confidence: 99%
“…where ci is equal to the corresponding confidence level (i.e., 68% = 1, 95% = 2, 99% = 3 Only gene names in common between the original data file and XPRESSpipe output were used for the method comparisons. Correlation between methods or replicates were calculated using a Spearman rank correlation coefficient, performed using the scipy.stats.spearmanr() function [32]. Pearson correlation coefficients were calculated using log 10 (rpm(counts) + 1) transformed data and the scipy.stats.pearsonr() function.…”
Section: Confidence Interval Plottingmentioning
confidence: 99%
“…Raw data were processed on a protected high-performance computing environment. Correlations between methods or replicates were calculated using a Spearman rank correlation coefficient, performed using the scipy.stats.spearman() function [32]. Interactive scatter plots were generated using Plotly Express [22].…”
Section: Tcga Data Analysismentioning
confidence: 99%
“…Traditionally, statistical-based co-expression indices have been used to calculate the dependencies between genes [ 5 , 7 ]. Some of the most popular correlation coefficients are Pearson, Kendall or Spearman [ 11 , 12 , 13 ]. Despite their popularity, statistical-based measures present some limitations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%